Results of Rehabilitation of Patients with Penetrating Wounds of the Eyeball - Jamshedovich, Ismailov Jasur (American Journal of Bioscience and Clinical Integrity, 2025)
The effectiveness of treating patients with penetrating wounds of the eyeball depends on the quality of specialized medical care. This includes both the full scope of primary surgical treatment of the wound and adequate conservative, surgical treatment of post-traumatic inflammatory complications, as well as professionally correct observation of patients with the consequences of penetrating wounds of the eye [1-4]. Outpatient observation of these patients is carried out mainly in outpatient clinics at the place of residence. Nevertheless, ophthalmologists of the outpatient clinic do not always have the opportunity (in terms of instrumental and laboratory equipment, the presence of appropriate specialization) to competently assess the severity of the injury and the prognosis of the course of the post-traumatic period, and are not always competent in resolving issues of surgical rehabilitation of these patients. One of the topical issues in ophthalmology is the problem of damage to the organ of vision. Studying the outcomes of treatment of penetrating eye wounds is of interest from the point of view of medical and, subsequently, social rehabilitation of this category of patients.